2023
DOI: 10.3390/su15020935
|View full text |Cite
|
Sign up to set email alerts
|

The Legal Transition towards a More Circular Electrical and Electronic Equipment Chain—A Case Study of The Netherlands

Abstract: The transition towards a circular economy in the EU requires that the legal framework does not create (legal) barriers, but rather enables or stimulates this transition. At this moment, however, the existing literature argues that the current legal system that governs the life cycle of materials and products—EU chemicals, product and waste legislation—might hamper the transition. This article looks into the legal framework for the transition of the product stream of electrical and electronic equipment (EEE) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…For example, a case study on the Packaging and Packaging Waste Directive found that the vague and unclear wording of the minimum design requirements for packaging made implementation and enforcement difficult in practice. 78 Altogether, although we are of the opinion that establishing minimum design and performance requirements would be beneficial, care must be taken to find a balance between setting sufficiently detailed criteria for sectors and products and avoiding excessively lengthy processes in establishing those.…”
Section: Design Of Productsmentioning
confidence: 99%
“…For example, a case study on the Packaging and Packaging Waste Directive found that the vague and unclear wording of the minimum design requirements for packaging made implementation and enforcement difficult in practice. 78 Altogether, although we are of the opinion that establishing minimum design and performance requirements would be beneficial, care must be taken to find a balance between setting sufficiently detailed criteria for sectors and products and avoiding excessively lengthy processes in establishing those.…”
Section: Design Of Productsmentioning
confidence: 99%